Retrospective Evaluation of Tourism Vocational School English Textbooks: Student Needs vs Curriculum Demands - Wedhanti, Nyoman Karina; Yuliasri, Issy; Pratama, Hendi; Sakhiyya, Zulfa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
The tourism industry requires every worker to have proficient English skills appropriate to their position. However, until now, tourism industry stakeholders still question the low communicative skills of tourism vocational school graduates in English. The study aims to critically evaluate the English language teaching materials used in tourism vocational high schools to analyze their suitability to student needs and the demands of the tourism industry. Using a retrospective evaluation methodology, data was carefully collected through documentation and interviews. Documentation is carried out to collect teaching materials used by schools, while interviews collect data regarding teachers' perceptions of these teaching materials. Qualitative data analysis was carried out using an interactive data analysis model. This research shows that although the material provided aligns with the national curriculum and focuses on everyday English communicative skills, the material still does not meet the particular needs of students preparing themselves for a career in the tourism sector. Teachers are aware of the significant gap between the general English skills taught and the specific English required of students. This study provides a basis for revising teaching materials to bridge this gap and ensure that they meet both general educational goals and the specific communicative demands of the tourism industry.